Typhlocybinae leafhoppers (Hemiptera, Cicadellidae) from Eocene Rovno amber reveal a transition in wing venation and a defensive adaptation. (March 2023) - Dietrich, Christopher H.; Simutnik, Serguei A.; Perkovsky, Evgeny E.
Abstract: The first fossil Typhlocybinae inclusions from Eocene Rovno amber are described and illustrated. They include two new monotypic genera of the extinct tribe Protodikraneurini, Retrorsotettix n. gen. with type species R. vlaskini n. sp. and Protoparallaxis n. gen. with type species P. clavatus n. sp. Also described and illustrated are two new monotypic genera of the extant tribe Dikraneurini, Eodikraneura n. gen. with type species E. obscura n. sp. and Rovnodikra n. gen. with type species Rovnodikra longipes n. sp. Retrorsotettix is the oldest leafhopper known to exhibit a false eyespot and false leg markings on the forewing, representing an early acquisition of a defensive strategy against visual predators. Appearance of a small insect with false eyespots in the Eocene fossil record may reflect increased pressure by visual predators, especially crown ornithuromorph insectivorous birds. Such birds and small insect prey with false eyespots remain unknown in the Cretaceous. Eodikraneura exhibits a unique condition of the hind wing venation in which radius posterior and media anterior veins are confluent for a short distance but then diverge before separately reaching the submarginal vein. This presumably represents a morphological transition between the Protodikraneurini, in which hind-wing radius posterior and media anterior veins are completely separate and connected by a radial-medial crossvein, and Dikraneurini, in which radius posterior and media anterior veins are completely confluent distally. A key to genera of Protodikraneurini is provided. UUID: http://zoobank.org/f15e6f80-9708-4f5e-89a3-705f9d340a77